OPTIMASI BIOKRAFT JAMUR Phanerochaete chrysosporium TERHADAP KOMPONEN KIMIA CAMPURAN BATANG DAN LIMBAH CABANG MANGIUM SEBAGAI BAHAN BAKU PULP - Devi Silsia; Ridwan Yahya; Mucharomah Mucharomah (Molekul, 2010)
Optimation biokraft of fungi P. Chrysosporium through elongated incubation time on mixed stem and branch waste mangium is a solution to solve the environmental pollution problem, low quality of pulp and limited raw material. Effect of P. Chrysosporium 10 % concentration and 45 days incubation time on pre research could not decrease lignin optimally and exstractive degradation had not occured yet. The aims of the study were to observe the effect of incubation time extension, and to determine the best incubation time of P. Chrysosporium applied at 10 % concentration based on the chemical component percentage, 45, 60 and 75 days on mixed stem and branch as raw material for pulp. Results showed that increasing incubation time decreased extractive and lignin content and increased holocelulosa and alpha celulosa content. Mixed stem and branch with 10% amount and 75 day incubation time of P. Chrysosporium gave the best results for raw material of pulp.